KONSEP RU'YAH ALLAH (S.W.T) DARI PERSPEKTIF PEMIKIRAN 'ALI BIN ABI TALIB (KW) - Prof. Madya Dr.Wan Zailan Karnaruddin (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
This article tries to discuss the vision of Allah Ru’ya Allah)from the perspertive of Ali's thought. ‘Ali bin Abi Talib is chosen because he is among the best Muslim thinkers after the demise of the Holy Prophet Muhammad (s.'a.w). The topic is quite relevant with our current Islamic Thought. Many relevant books used in this article in order to get a clear picture on ‘Ali's viewpoints, and the best to be referred to is Kitab Nahj al-Balaghah. It conprises the sayings of ‘Ali bin Abi Talib, as collected by al-Sharif al-Radi. Although there will be different views and opinions among Muslim thinkers from various sects on the topic, but generally they agreed that ‘Ali is the best scholar to refer to. Hopefully, this article will benefit Muslims in malaysia and elsewhere",